Gender differences among patients with drug resistant tuberculosis and HIV co‑infection in Uganda: a countrywide retrospective cohort study - Baluku, Joseph Baruch; Mukasa, David; Bongomin, Felix; Stadelmann, Anna; Nuwagira, Edwin; Haller, Sabine; Ntabadde, Kauthrah; Turyahabwe, Stavia (BMC Infectious Diseases, 2021)
Background: Gender differences among patients with drug resistant tuberculosis (DRTB) and HIV co-infection could affect treatment outcomes. We compared characteristics and treatment outcomes of DRTB/HIV co-infected men and women in Uganda. Methods: We conducted a retrospective chart review of patients with DRTB from 16 treatment sites in Uganda. Eligible patients were aged ≥ 18 years, had confirmed DRTB, HIV co-infection and a treatment outcome registered between 2013 and 2019. We compared socio-demographic and clinical characteristics and tuberculosis treatment outcomes between men and women. Potential predictors of mortality were determined by cox proportional hazard regression analysis that controlled for gender. Statistical significance was set at p < 0.05. Results: Of 666 DRTB/HIV co-infected patients, 401 (60.2%) were men. The median (IQR) age of men and women was 37.0 (13.0) and 34.0 (13.0) years respectively (p < 0.001). Men were significantly more likely to be on tenofovir-based antiretroviral therapy (ART), high-dose isoniazid-containing DRTB regimen and to have history of cigarette or alcohol use. They were also more likely to have multi-drug resistant TB, isoniazid and streptomycin resistance and had higher creatinine, aspartate and gamma-glutamyl aminotransferase and total bilirubin levels. Conversely, women were more likely to be unemployed, unmarried, receive treatment from the national referral hospital and to have anemia, a capreomycin-containing DRTB regimen and zidovudine-based ART. Treatment success was observed among 437 (65.6%) and did not differ between the genders. However, mortality was higher among men than women (25.7% vs. 18.5%, p = 0.030) and men had a shorter mean (standard error) survival time (16.8 (0.42) vs. 19.0 (0.46) months), Log Rank test (p = 0.046). Predictors of mortality, after adjusting for gender, were cigarette smoking (aHR = 4.87, 95% CI 1.28–18.58, p = 0.020), an increase in alanine aminotransferase levels (aHR = 1.05, 95% CI 1.02–1.07, p < 0.001), and history of ART default (aHR = 3.86, 95% CI 1.31–11.37, p = 0.014) while a higher baseline CD4 count was associated with lower mortality (aHR = 0.94, 95% CI 0.89–0.99, p = 0.013 for every 10 cells/mm3 increment). Conclusion: Mortality was higher among men than women with DRTB/HIV co-infection which could be explained by several sociodemographic and clinical differences.
Keywords: Gender differences; TB/HIV; MDR; Mortality; Men; Women; Drug resistance; Tuberculosis; Sex